Pembekalan Bisnis Digital bagi Angkatan Muda Muhammadiyah Kabupaten Bogor - Zulpahmi, Zulpahmi; Sumardi, Sumardi; Setiawan, Edi (Faculty of Economics and Business, University of Muhammadiyah Prof. DR. HAMKA, 2018)
Building a business through the Internet or so-called digital business is one way to expand the market reach of business people. Through online marketing, product information can reach consumers far away from domicile, without having to go directly to the area to promote the product. Thus, the opportunity for Muhammadiyah citizens in establishing and managing an online business is huge. In order to be able to establish and manage an online business properly and properly, adequate knowledge and skills are required. Thus, it is necessary to have a briefing in building a digital business for the youth Muhammadiyah Youth Bogor Regency. This program is intended to improve the ability to develop online business.